USE OF PROBLEM-BASED LEARNING (PBL) MODEL TO IMPROVE LEARNING OUTCOMES IN ENVIRONMENTAL EDUCATION - Rachman, Indriyani; Sugimaru, Chika; Matsumoto, Toru (UI Scholars Hub, 2020)
Wastewater and household trash have become serious problems in major Indonesian cities due to the lack of environmental education for children and society as a whole. This paper will examine the urban lifestyle and the processing of waste, followed by an analysis of problem-based learning (PBL) experiments in elementary schools in various cities. The analysis will be supplemented with a questionnaire distributed to the students before and after the PBL trial. The article aims to offer an alternative educational environment that will evoke maximum learning results. It has been prepared using cross-tabulation research methods for three groups: The first group is comprised of students and teachers who have studied environmental education using the PBL method and through workshop activities. The second group comprises teachers who have studied environmental education using workshop activities. The third group includes teachers and students who have studied environmental education without the PBL model or workshop activities. Using cross-tabulation, show that the proportion of respondents increased after implementation compared to before is hand both Groups A and B. Group C does not show much change after implementation. From this study, authors conclude that groups using the PBL learning model with workshops showed significant changes in knowledge aspects.